(untitled) (Journal of NELTA, 2013)
Homework is a good means of reactivation; it helps students to practice language items and consolidates learnt knowledge and skills at their home. It is an indispensible tool for students to step forward in the subject. But if we glance at homework dealing situation at school level education in Nepal, the role of homework is hardly talked about in the majority of the schools, especially at government aided school. Similarly, if we look at researches and papers that are talked about on homework dealing situation at school level education, we will rarely find. For this reason, I have strived to explore homework dealing situation of English langauge teaching at grade eight in Dadeldhura District through survey questions to the students and the teachers, such as when do students feel difficult to do homework, why do they do homework, how much time do they spend to do homework, who does help them to do homework at home, how do they like their homework to be corrected, how do the teachers correct homework, and the like. It also suggests some strategies for increasing homework completion rates and making homework meaningful for the students. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 50-60 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8092